The paradoxical reality of racism: German soccer and the irreversibility of multiculturalism - Koch, A. (Soccer & Society, 2023)
This paper analyzes three domains of German soccer and their role within debates about multiculturalism and race: The vernacular culture as intersection of fan culture and racism highlighted by attacks from the political right; the culture industry`s investigation into the alleged false identity of Bakery Jatta; and soccer`s occupational culture with a focus on racial abuse and denial within both playing and coaching arenas. The contrast of these three discourses reveals that German soccer at once presents itself as a harmonious multicultural microcosm while failing to grasp enduring challenges of racism. But it suggests also that despite claims of a failure of multiculturalism, German soccer may in fact be at the fore of showing German multiculturalism as an irrevocable, if highly contested reality.